2004
DOI: 10.1016/s0197-4580(03)00085-x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate transporters in platelets: EAAT1 decrease in aging and in Alzheimer’s disease

Abstract: Platelets release glutamate upon activation and are an important clearance system of the amino acid from blood, through high-affinity glutamate uptake, similar to that described in brain synaptosomes. Since platelet glutamate uptake is decreased in neurodegenerative disorders, we performed a morphological and molecular characterization of platelet glutamate transporters. The three major brain glutamate transporters EAAT1, EAAT2 and EAAT3 are expressed in platelets, with similar molecular weight, although at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 51 publications
(64 reference statements)
2
38
1
Order By: Relevance
“…Amyotrophic lateral sclerosis is a relatively frequent neurodegenerative disease that affects both upper and inferior motoneurons. Reduced glutamate (Glu) transporter, EAAT1, has been described in lateral amyotrophic sclerosis (ALS) tissues in 1995 [14], and recently demonstrated in aging and AD [15]. Looking for the effects of the excitatory aminoacid Glu on neurons, especially on the calcium mediated synthesis of nitric oxide (NO), we found that nitrites and nitrates, as end-products of NO, are measurable in the CSF [16].…”
Section: Introductionmentioning
confidence: 71%
“…Amyotrophic lateral sclerosis is a relatively frequent neurodegenerative disease that affects both upper and inferior motoneurons. Reduced glutamate (Glu) transporter, EAAT1, has been described in lateral amyotrophic sclerosis (ALS) tissues in 1995 [14], and recently demonstrated in aging and AD [15]. Looking for the effects of the excitatory aminoacid Glu on neurons, especially on the calcium mediated synthesis of nitric oxide (NO), we found that nitrites and nitrates, as end-products of NO, are measurable in the CSF [16].…”
Section: Introductionmentioning
confidence: 71%
“…EAAT3 is not only expressed in neurons [28,[51][52][53][54][55][56][57], retinal ganglion cells [58] and glial cells [59,60] but is expressed in a wide variety of nonexcitable cells and non-neuronal tissues including blood platelets [61,62], heart [63], renal podocytes [64], epididymis [65], placenta [66,67] and blood-brain barrier [68].…”
Section: Discussionmentioning
confidence: 99%
“…Results are relevant to the understanding of the mechanisms of excitotoxicity involved in neuronal damage associated with ischemia and some neurodegenerative diseases. While acute transport-mediated glutamate release and energy depletion are associated with ischemia and hypoglycemia [9,52] chronic failure of glutamate uptake might be associated with Huntington's and Alzheimer's diseases [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, decreased glutamate uptake and expression of glutamate transporters has been associated with Alzheimer's and Huntington's diseases, and excitotoxicity has been suggested as a component of the process of neurodegeneration linked to these pathologies [15][16][17][18][19]. Studies have shown that decreased expression of glutamate transporters in vivo, promotes the extracellular accumulation of glutamate and neuronal death [20,21].…”
Section: Introductionmentioning
confidence: 99%